PELATIHAN PEMBUATAN CRACKERS MODIFIKASI F100 DENGAN SUBSTITUSI TEPUNG LABU KUNING BAGI TENAGA GIZI PENDAMPING GIZI BURUK - Ria Ambarwati; Yuwono Setiadi; Susi Tursilowati; Ana Yuliah Rahmawati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2018)
Results of the monitoring and evaluation of programs comprehensive examination malnutrition children in the city of Semarang, 2014 shows a toddler can not spend PMT, one reason is the toddler suffering from boredom, so that changes in nutritional status and the expected weight gain cannot be achieved is not expected to be achieved so as to consider alternative forms of formulas for children malnutrition. The alternative to the manufacture of food in the form of crackers by using basic ingredients WHO F100 formula with flour substitute pumpkin. Ria and Yuwono study (2016) that cRackers with basic materials modification F100 with pumpkin flour substitution of 10% can be accepted by a toddler. Provide training on making crackers modified F100 with pumpkin flour substitution on energy malnutrition nutrition assistant at Home Nutrition Semarang. The training methods include lectures, practice and assessment discussion participants include taste, aroma, colour and texture Most participants (80%) were able to make modifications crackers F100 pumpkin flour substitution. Acceptance test conducted by the participants of the colour of 3.56, 3.14 aroma, flavour and texture 3,12 3.44. Crackers modified F100 with pumpkin flour substitution can be used as an alternative food supplement for children with malnutrition.